AGAMA DAN PERSOALAN-PERSOALAN IPTEK (Upaya Memadukan Ilmu Pengetahuan dan Agama) - Zainuddin Hamkah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
Between Religion and Science there should not be a dichotomy that must go hand in hand, in harmony and in balance because science and technology can only be of maximum benefit to humans if the person who owns it is a religious (moral) person. Science and Technology that is not framed or limited by Religion or Morals will only add sophistication to the way humans destroy civilization. Several incidents and events have shown among them America has dropped atomic bombs on the densely populated cities of Hiroshima and Nagasaki, Japan at the end of World War II. And besides that, the American invasion of Iraq a few years ago, all of which shows how evil Science and Technology is developing among people who have no religion (moral). Actually, if only humans, especially Muslims, followed Allah's instructions, of course Science and Technology would not be a disaster for humans if they were limited by religion (morals). The development of science and technology will provide the greatest benefit to humans.